Aplikasi Pemasaran Sampah Anorganik Sebagai Bahan Baku Pengolahan Sampah Berkelanjutan - Budiman, Marson James; Pongoh, Deitje Sofie; Lambonan, Oldi Malfri (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2024)
This website-based inorganic waste marketing application has the potential to make a positive contribution to more sustainable waste management, by facilitating more efficient waste collection and sales practices. Apart from that, this application also has the potential to increase environmental awareness among the public. This research aims to design and develop a website-based marketing application for Inorganic Waste using the SDLC (Software Development Life Cycle) Development Method. This application was built as a solution to facilitate more efficient and sustainable waste management. The SDLC method is used as a framework in developing this application, which includes the stages of planning, needs analysis, design, development, testing, implementation and maintenance. The results obtained through system testing using the black box method are that the system can run the home window menu, trash buying feature, trash selling feature, transaction feature, point exchange feature, trash list feature, order feature, offer feature, and report feature. This system is a practical solution for MSME business actors who process inorganic waste.